NTC's english idioms dictionary - Spears, Richard A.; Kirkpatrick, Betty (Lincolnwood, Ill. : NTC Publishing Group, 1998)
Language and Literature
Keywords: Dictionaries; Idioms-Dictionaries; English idioms-Dictionaries